OPPORTUNITIES OF MEDIA EDUCATION IN THE PATRIOTIC EDUCATION OF STUDENT’S YOUTH - Maria V. Guzeva; Olga V. Leonova (Вестник Северо-Кавказского федерального университета, 2022)
This paper presents an experimental study devoted to the isolation and testing of the conditions for successful educational work on the formation and development of patriotism among students by means of mass media. The main directions in the understanding of the phenomenon of patriotism, highlighted aspects of the process of formation of patriotism.